Strategy choice for agricultural green transformation in China from system dynamics perspective - Pan, Meixi; Zhao, Guishen (Frontiers in Sustainable Food Systems, 2025)
China faces multiple pressures on productivity enhancement, ecological protection and livelihood improvement, and how to reconcile these objectives is an important consideration in the choice of strategies for agricultural green development. In this study, we try to propose a comprehensive approach to consider multiple objectives of agricultural green development from a system dynamics perspective, which aims to identify the synergies and trade-offs among objectives under different scenarios in the National Pilot Zones for Green Development of Agriculture in China, and Xuzhou City and Nanping City are selected as two different target areas. The research demonstrates that system dynamics modeling can effectively facilitate strategic choices for decision-makers. There are upward trends in the system in terms of the agricultural improvement index, gross food production, and farmers’ income in the two target pilot zones, which can achieve overall synergy before 2030, although a trade-off relationship between food production and environmental protection. Furthermore, the agricultural green transformation index based on different scenarios could guide strategic choices. Xuzhou in economically prosperous zones has a leading level of index for the green transition scenario (reaching 83.76 in 2030, surpassing the other two scenarios), and shows greater potential to prioritize green transition for high-quality development. Meanwhile, the business-as-usual scenario for economically less-developed city of Nanping has the highest index of 97.61 in 2030, indicating the need for supportive policies to maintain the agricultural transition process. In brief, strategic decisions for green transformation in China should be based on the structural characteristics and development goals of the agricultural system, with an emphasis on both short-term progress and long-term trends.